Detailed physical property investigation study on ZnO NPs containing waste PS-PLA smart polymeric composites: crystal structure, thermal, optical properties and radiation shielding behavior - Tatar, Cengiz; Kok, Mediha; Dogru, Mahmut; Coskun, Meltem; Oner, Ecem Ozen (Polymer Soc Korea, 2025)
Today, scientists are working on researching ergonomic, economical materials with protective properties that will make our lives easier. The demand for polymers that exhibit smart properties as well as their cost-effective and lightweight properties is increasing day by day. Giving these materials electrical properties and radiation protection means that many properties can be satisfied with a single material. In this study, ZnO, a semiconductor, was doped at different ratios into a mixture of PLA, a shape memory polymer (smart polymer), and PS, a waste polymer, and its physical properties were investigated in detail. ZnO/polymer blend composite was found to have the bond structures of polymers. It was observed that the crystalline properties of the polymeric composite were determined by ZnO doping, which exhibited a crystal structure. Thermal measurements showed that zinc oxide did not change the phase transformation temperature of the polymeric blend, however, the mass change percentage decreased and the thermal stability increased. The remaining mass was found to be around 30% in the composite containing 40% ZnO. According to the results of optical property measurements, PS-PLA polymers were found to shift from the UV region to the visible region with ZnO and it was also found that the band energy value decreased below 4 eV by adding ZnO and the highest ZnO-containing composite was 3.36 eV. Therefore, it is concluded that the composites exhibit semiconducting properties. The spectroscopy results showed that for 661 keV, the linear absorption capacity in the polymeric composite increased from 0.65 cm-1 to 2.29 cm-1 with increasing ZnO percentage, which can be interpreted as an increase in shielding capability.Graphical AbstractProduction of ZnO doped polymer blend
Keywords: Smart polymer; Zinc Oxide; Radiation Shielding; Semiconductor Material